Shear strength of reinforced recycled aggregate concrete beams without shear reinforcements - Choi, Won-Chang; Yun, Hyun-Do (Journal of Civil Engineering and Management, 2017)
As the demand for sustainable construction materials has risen over recent years, researchers have conducted several studies to expand the practical application of recycled construction materials, such as recycled aggregate. The author’s previous research shows the potential application of recycled aggregate over a broad range of structural member types. This paper continues the earlier work and investigates the shear behaviour of reinforced recycled aggregate concrete beams without shear reinforcement using findings from the author’s previous research. The variables in the test program are replacement rate (0%, 30%, 60%, and 100%) of recycled aggregate and shear span-to-depth ratio (2.0, 2.5, 3.0, 4.0, and 5.0). This work compares the experimental results with results obtained using current code equations found in American Concrete Institute (ACI) 318 (2014) and equations proposed in the literature. This research has found that the current code equations can adequately predict the shear strength of recycled coarse aggregate concrete beams and possibly can be applied for the use of recycled aggregate in structural elements. First published online: 01 Jul 2016